Dinosaurs travel : a guide for families on the go - Brown, Laurene Krasny; Brown, Marc Tolon (Boston : Joy Street Books, 1988)
Text and illustrations of dinosaur characters discuss the practicalities and pleasures of travel, from packing up and taking off to returning home again.
Keywords: Travel